Distribusi dalam Kajian Ekonomi Islam - Sari, Narulita (EJESH: Journal of Islamic Economics and Social, 2023)
In Islamic economics, research on distribution has always been a heated debate because it talks not only about economic aspects but also about social and political aspects. Therefore, to this day, this research has attracted the attention of Islamic and conventional economic thinkers. This qualitative descriptive research is being done. The purpose of this research is to interpret and provide an explanation of data related to current circumstances, public perspectives and attitudes, conflicts between two or more situations, influences on certain conditions, and other factors. To lay the theoretical foundations for this qualitative descriptive research, researchers used library studies to gather information from books, magazines, newspapers, and other literature. The results of the journal show that the distribution of income and wealth is based on timeliness and time limits, whereas income distribution is based upon production, barter, and market considerations. Redistribution, which is commonly called social transformation, is based on religious, moral, family, and social considerations.